36 Human parahippocampal cortex supports spatial binding in visual working memory. Issue 8 (13th July 2017) - Katshu, Mohammad Zia Ul Haq; Dundon, Neil Michael; Harry, Bronson; Roberts, Daniel; Leek, ECharles; Downing, Paul; Roberts, Craig; d'Avossa, Giovanni
Abstract : Objective: Studies investigating the functional organisation of the medial temporal lobe (MTL) suggest that parahippocampal cortex (PHC) generates representations of spatial and contextual information used by the hippocampus in the formation of episodic memories. However, evidence from animal studies also implicates PHC in spatial binding of visual information held in working memory. This study focussed on elucidating the role of PHC in spatial binding in working memory in humans. Method: We assessed a 46-year-old man (PJ), after he had recovered from bilateral medial occipitotemporal cortical mOTC strokes resulting in lesions in PHC but sparing the hippocampus, and a group of age-matched healthy controls on a series of visual working memory tasks. Results: When recalling the colour of one of two objects, PJ misidentified the target when cued by its location, but not shape. When recalling the position of one of three objects, he frequently misidentified the target, which was cued by its colour. Increasing the duration of the memory delay had no impact on the proportion of binding errors, but did significantly worsen recall precision in both PJ and controls. Conclusion: We conclude that PHC plays a crucial role in spatial binding during encoding of visual information in working.